2020
DOI: 10.3390/su12156286
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Alleviation by ACC Deaminase Producing Achromobacter xylosoxidans and Enterobacter cloacae, with and without Timber Waste Biochar in Maize

Abstract: The high consumption of water in industries, domestic areas and increasing earth temperature are major hurdles for the optimization of maize yield. Being the third most widely cultivated cereal crop, improvement in maize yield is a big challenge under the limited availability of irrigation. As the water requirement for maize cultivation is high, it is time to introduce technologies that can mitigate drought stress and are environmentally friendly. The inoculation of rhizobacteria with ‘1-aminocyclopropane-1-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 80 publications
2
40
0
Order By: Relevance
“…The plant roots and the microbial community influence each other [ 85 ]. Soil rhizobacteria plays an significant in nutrient uptake and plant growth [ 86 , 87 , 88 , 89 , 90 ]. Hamidi and Marashi [ 91 ] showed that increasing the use of phosphorus fertilizer and the use of mycorrhizal fungi can be effective in achieving the desired yield of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…The plant roots and the microbial community influence each other [ 85 ]. Soil rhizobacteria plays an significant in nutrient uptake and plant growth [ 86 , 87 , 88 , 89 , 90 ]. Hamidi and Marashi [ 91 ] showed that increasing the use of phosphorus fertilizer and the use of mycorrhizal fungi can be effective in achieving the desired yield of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Among all abiotic stresses (heavy metals [1][2][3][4][5][6], salinity [7], nutrient deficiency [8,9]), drought is the most severe stress [10] that decreases crop production in various world climatic regions [11,12]. A drastic reduction (50%) in the yield of crops occurs annually due to soil water deficiencies [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Among all, some rhizobacteria are capable to produce ACC deaminase that has the potential to decrease the stress generating ethylene in the plants. Recent studies indicated that rhizobacteria having ACC deaminase are helpful to mitigate the adverse effects of stress generating ethylene [8][9][10][11][12][13][14] . Enzyme 1-aminocyclopropane-1-carboxylate deaminase (ACCD), can break ACC, (an immediate precursor of ethylene) to ammonia and α-ketobutyrate 15 .…”
mentioning
confidence: 99%